International Aspects of Civil Strife - Rosenau, James N. (Princeton, NJ : Princeton University Press, 2015)
This exploration of a vital issue includes: "The International Relations of Internal War," G. Modelski; "Internal War as an International Event," J. N. Rosenau; "Intervention in Internal War: Some Systemic Sources," M. A. Kaplan; "International Settlement of Internal War," G. Moclelski; "Internal Violence as an Instrument of Cold Warfare," A. M. Scott; "The Limits of International Blocs, States, Coalitions, and Negotiating Programs," K. W. Deutsch and M. A. Kaplan; "Janus Tormented: The International Law of Internal War," H. A. Falk; "The Morality and Politics of Intervention," M. Halpern; and "International Aspects of Internal War: A Working Paper," J. N. Rosenau.Originally published in 1964.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Acknowledgments -- Contents -- 1. Introduction / Rosenau, James N. -- 2. The International Relations of Internal War / Modelski, George -- 3. Internal War as an International Event / Rosenau, James N. -- 4. Intervention in Internal War: Some Systemic Sources / Kaplan, Morton A. -- 5. International Settlement of Internal War / Modelski, George -- 6. Internal Violence as an Instrument of Cold Warfare / Scott, Andrew M. -- 7. The Limits of International Coalitions / Deutsch, Karl W. / Kaplan, Morton A. -- 8. Janus Tormented: The International Law of Internal War / Falk, Richard A. -- 9. The Morality and Politics of Intervention / Halpern, Manfred -- Appendix A. International Aspects of Internal War: A Working Paper / Rosenau, James N. -- Contributors -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Civil war; POLITICAL SCIENCE / International Relations / General